Virtual connectivity in mediating millennials destination emotional experience - Mohd, Nur Shuhadah; Ismail, Hairul Nizam; Isa, Norliza; Syed Jaafar, Syed Muhammad Rafy (Universiti Teknologi Malaysia, 2018)
Millennial is known to be the generations that strongly empowered by technologies that apparently had altered the pattern of their consumption habits to shape a new form of tourist market. The great incursion of technology on millennial does not only mediates the experience formation at destination, instead provide added value and emotional impact through its cognitive stimulation and experience co-creation possibilities. As the key instrument for experience enhancement, mobile technologies support users' needs of on-site information, virtually connect tourism providers and consumers, and unfold destination uniqueness. These in turn allow co-creation of tourist experience through satisfaction of millennial's addiction of connectivity. Virtual connectivity seems to create new form of affective attachment, through which millennial are emotionally bonded to the place due to the intensity of technological engagement. Consequently, instead of tourist-destination encounter per se, technological experience is potentially classified as the third aspects that dictate experience development, especially among millennial travellers. Existing literatures indicates that millennial strong engagement with virtual platform is capable to manipulate their on-site emotional experience, which apparently changing the conventional way of tourist experiencing the destination. Nevertheless, the significant of millennial's technological engagement towards their destination emotional experience is still open for debates. Pertaining to this situation, this conceptual paper is attempted to understand the influence of technology in the enhancement of emotional experience, specifically among millennial travellers, in better understanding the evolving demand of the new generations tourist from psychological perspective.